PENGARUH KOMPETENSI APARATUR DESA, KETAATAN PELAPORAN KEUANGAN DAN SISTEM PENGENDALIAN INTERN TERHADAP PENCEGAHAN FRAUD DENGAN MORAL SENSITIVITY SEBAGAI VARIABEL MODERASI - Wonar, Klara; Falah, Syaikhul; Pangayow, Bill J. C. (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This study aims to examine the effect of fraud prevention on village / village financial management as the dependent variable and the competency of village apparatuses, compliance of government financial reporting, internal control systems as independent variables while moral sensitivity as amoderating variable. This research is a quantitative research or hypothetic - deductive method that aims to answer such questions that are related to exploratory, descriptive, explanatory and predictive studies. Primary data is mainly used in this research. Data collection is conducted using a survey method in the form of a questionnaire that lists the statements, which were given to the respondents to be filled in order to get information, and then the data analyzing was conducted using the Warp-PLS 5.0 Application software. The study results show that the competence of village officials influences fraud prevention, financial reporting adherence affects fraud prevention, and meanwhile the internal control system does not affect fraud prevention. Furthermore, moral sensitivity does not moderate the competence of village officials, adherence to financial reporting and internal control systems.